(Samo)spoznaja u odnosu spram Drugoga i strana kultura kao izvor vlastita identiteta: pjesnik Zdravko Malić / (Samo)poznanie wobec Innego i kultura obca jako źródło własnej tożsamości: poeta Zdravko Malić (tłum. Katarzyna Majdzik) - Rogić Musa, Tea (Przekłady Literatur Słowiańskich, 2016)
(Self‑) perception in regards to the Other and foreign culture as a source of one’s own identity: the poet Zdravko Malić This paper deals primarily with the poetry of Zdravko Malić, one of the most prominent Croatian Polonists of the 20th century, founder of Croatian Polonistics as a university, institutionalised philological discipline, and the author of a comprehensive and far‑reaching literary‑historic and translator’s body of work. Along with his literary‑scientific work and work as a translator, as a poet Malić wrote a rather small but, in the composition of the whole of his interests, an indicative poetic contribution, which mirrors his research topics and the depth of their perception. As a Polonist, he covered his own poetic practice with a web of intertextual and citation points that helped him to refer to a foreign culture, Polish, as the starting point of his erudition. As a prolegomenon to the insight into his poetic collection, we will give a brief overview of Malić’s body of work and his activities, which supplements his biography as a Polonist. Key words: Zdravko Malić, U drugom nekom gradu, prose poem, Croatian‑Polish literary connections